Identification of active sites and reaction mechanism on low-temperature SCR activity over Cu-SSZ-13 catalysts prepared by different methods. Issue 16 (6th June 2016) - Zhang, Tao; Qiu, Feng; Chang, Huazhen; Li, Xiang; Li, Junhua
Abstract : Cu-SSZ-13 catalysts with similar Si/Al and Cu/Al ratios were prepared by aqueous solution ion-exchange (Cu-SSZ-13-I) and one-pot synthesis (Cu-SSZ-13-O) methods. Abstract : Cu-SSZ-13 catalysts with similar Si/Al and Cu/Al ratios were prepared by aqueous solution ion-exchange (Cu-SSZ-13-I) and one-pot synthesis (Cu-SSZ-13-O) methods. NH3 -SCR tests, XRD, BET, SEM, HRTEM, EPR, H2 -TPR, NH3 -TPD, NO + O2 -TPD, in situ DRIFTS, and kinetic tests were performed for the catalytic measurement, bulk characterization and mechanism estimation. The NH3 -SCR results indicated that Cu-SSZ-13-O showed higher DeNO x activity than Cu-SSZ-13-I in the absence or presence of H2 O across the entire temperature range. The results of EPR, H2 -TPR and NO + O2 -TPD showed that more Cu 2+ ions existed in Cu-SSZ-13-O, which mainly accounts for the Lewis acid sites and the majority of the NO x adsorption or activation. The DRIFTS results showed that NH3 on Lewis acid sites was more active than that on Brønsted acid sites in the NH3 -SCR reaction. Furthermore, the DRIFTS results also indicated that monodentate nitrates are the most active nitrate species. Compared with Cu-SSZ-13-I, Cu-SSZ-13-O showed stronger Lewis acid site strengths and had more abundant monodentate nitrate species. Therefore, the NH3 -SCR reaction proceeded more easily over Cu-SSZ-13-O in comparison with Cu-SSZ-13-I. This could be the key factor that explains the more excellent low-temperature SCR activity of Cu-SSZ-13-O. In addition, at low reaction temperatures, Cu-SSZ-13-O was less affected by pore ( i.e., intracrystalline) diffusion limitations.